2015
DOI: 10.1007/s10549-015-3645-3
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin prevents triple-negative breast cancer metastasis in pre-clinical models through regulation of FOXO3a

Abstract: Purpose We previously reported using statins was correlated with improved metastasis free survival in aggressive breast cancer. The purpose of this study was to examine the effect of statins on metastatic colonization by triple negative breast cancer (TNBC) cells. Experimental Design TNBC cell lines were treated with simvastatin and then studied for cell cycle progression and proliferation in vitro, and metastasis formation in vivo, following injection of statin-treated cells. Reverse-phase protein assay (RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…inactivate FOXO3A and its target, estrogen receptor-a, in turn removing a block on c-Rel to mediate mammary tumorigenesis (32). Interestingly, our team showed that simvastatin, which promotes radiosensitivity of IBC cells (33), prevents breast cancer metastasis via stabilization of FOXO3A (34). This work suggests the promise for IBC of combination therapeutic approaches that include drugs that educate the tumor microenvironment in patients with indication of M2 macrophage activation.…”
Section: Discussionmentioning
confidence: 77%
“…inactivate FOXO3A and its target, estrogen receptor-a, in turn removing a block on c-Rel to mediate mammary tumorigenesis (32). Interestingly, our team showed that simvastatin, which promotes radiosensitivity of IBC cells (33), prevents breast cancer metastasis via stabilization of FOXO3A (34). This work suggests the promise for IBC of combination therapeutic approaches that include drugs that educate the tumor microenvironment in patients with indication of M2 macrophage activation.…”
Section: Discussionmentioning
confidence: 77%
“…To date, many drugs associated with obesity such as lipid-lowering (statins) or antidiabetic drugs (metformin) have been used in cancer treatment with good effects (Brown, 2007;De Queiroz et al, 2015;Hager et al, 2006;Hanai et al, 2012;Wang et al, 2014). Appropriately, it has been demonstrated that both statins and metformin are able to increase the activity of FOXO3 (De Queiroz et al, 2015;Wolfe et al, 2015), whereas metformin is also able to inhibit the expression of FOXM1 . Collectively, these observations advocate further that targeting lipid metabolism in conjunction with the FOXO3-FOXM1 axis maybe a viable strategy for tackling cancer development, progression and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have implicated cholesterol regulation in both the risk and progression of breast cancer 6 . Our lab and others have shown that cholesterol regulation can influence pre-clinical models of triple negative breast cancer through a PI3K/FOXO3a pathway, affecting stem cells and metastases 7 - 9 .…”
Section: Introductionmentioning
confidence: 87%